Law, politics, and morality in Judaism - Walzer, Michael (Princeton University Press, 2006)
Jewish legal and political thought developed in conditions of exile, where Jews had neither a state of their own nor citizenship in any other. What use, then, can this body of thought be today to Jews living in Israel or as emancipated citizens in secular democratic states? Can a culture of exile be adapted to help Jews find ways of being at home politically today? These questions are central in Law, Politics, and Morality in Judaism, a collection of essays by contemporary political theorists, philosophers, and lawyers. --From publisher's description.
Keywords: Jewish law -- Moral and ethical aspects.; Public law (Jewish law); Judaism and state.; Law -- Israel -- Jewish influences.; Droit juif -- Aspect moral.; Judaïsme et État.; RELIGION -- Judaism -- Theology.; POLITICAL SCIENCE -- History & Theory.; Jewish law -- Moral and ethical aspects; Judaism and state; Law -- Jewish influences; Israel; Jüdisches Recht; Öffentliches Recht; Judentum; Joods recht.; Politiek.; Ethiek.